7z+4-3z=46-3z

Simple and best practice solution for 7z+4-3z=46-3z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7z+4-3z=46-3z equation:


Simplifying
7z + 4 + -3z = 46 + -3z

Reorder the terms:
4 + 7z + -3z = 46 + -3z

Combine like terms: 7z + -3z = 4z
4 + 4z = 46 + -3z

Solving
4 + 4z = 46 + -3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '3z' to each side of the equation.
4 + 4z + 3z = 46 + -3z + 3z

Combine like terms: 4z + 3z = 7z
4 + 7z = 46 + -3z + 3z

Combine like terms: -3z + 3z = 0
4 + 7z = 46 + 0
4 + 7z = 46

Add '-4' to each side of the equation.
4 + -4 + 7z = 46 + -4

Combine like terms: 4 + -4 = 0
0 + 7z = 46 + -4
7z = 46 + -4

Combine like terms: 46 + -4 = 42
7z = 42

Divide each side by '7'.
z = 6

Simplifying
z = 6

See similar equations:

| 3c^2-24c=0 | | 4.7q-5.6-4.3q=-0.6q-1.4 | | 8x+1=7x | | 6x^3-10x^2+12x-21=0 | | (n-5)(n+12)=0 | | 3(1+c)=2(c-3) | | 3w^2-22w=16 | | 10(8c-1)-18=78c+10 | | 19x+(-8)=-44+10x | | 4/a=b/2 | | 5(y-2)=2y-9 | | x^2+(y)x+(y^2-19)=0 | | x^2+xy+y^2=19 | | 4-4x=11+3x | | -6n+5=-5n-11 | | -4y-12=5y+42 | | 8y-2=3y+3 | | 5c+12=7c+10.82 | | (-4a)+3=2a+12 | | -5+12=15x-3-14x | | 7y-12y=-26-34 | | -9.1y=-283.92 | | -8c+7=-9 | | 8=9w+3/2+5w+7/6 | | 5*14= | | 68+100+100= | | 6x^2+7x-13=0 | | -1/x^2=0 | | -1/x^2 | | 2(7x-4)+4x=4x-8+14x | | 9x+4=7x+7 | | 3(3x-5)+3x=4x-17+8x |

Equations solver categories